Unveiling Genital Tuberculosis: India’s hidden Infertility Epidemic - Yashvanthan VR; Angeline Grace G; Sujitha P; Ilam Ilaval T; Hariharan S (National Journal of Community Medicine)
Genital tuberculosis (GTB) is a significant yet underrecognized cause of infertility, particularly in high-burden countries like India. It often presents asymptomatically or mimics other reproductive disorders, leading to delayed diagnosis and treatment. GTB primarily affects women of reproductive age but can also impact men, contributing to infertility through various pathophysiological mechanisms. Despite its prevalence, GTB remains a hidden epidemic due to limited awareness, diagnostic challenges, and systemic healthcare gaps. This narrative review explores the epidemiology, pathophysiology, clinical presentation, and impact of GTB on infertility in India. It also highlights diagnostic and management challenges while proposing strategies to address this critical public health issue.